The Effect of Oxidative Stress and Antioxidant Therapies on Pancreatic β-cell Dysfunction: Results from in Vitro and in Vivo Studies - Anastasiou, Ioanna A.; Eleftheriadou, Ioanna; Tentolouris, Anastasios; Koliaki, Chrysi; Kosta, Ourania A.; Tentolouris, Nikolaos (Current Medicinal Chemistry, 2021)
Background: Oxidative stress is a hallmark of many diseases. A growing body of evidence suggests that hyperglycemia-induced oxidative stress plays an important role in pancreatic β-cells dysfunction and apoptosis, as well as in the development and progression of diabetic complications. Considering the vulnerability of pancreatic β-cells to oxidative damage, the induction of endogenous antioxidant enzymes or exogenous antioxidant administration has been proposed to protect pancreatic β-cells from damage. Objectives: The present review aims to provide evidence of the effect of oxidative stress and antioxidant therapies on pancreatic β-cell function, based on in vitro and in vivo studies. Methods: The MEDLINE and EMBASE databases were searched to retrieve available data. Results: Due to poor endogenous antioxidant mechanisms, pancreatic β-cells are extremely sensitive to Reactive Oxygen Species (ROS). Many natural extracts have been tested in vitro in pancreatic β-cell lines in terms of their antioxidant and diabetes mellitus ameliorating effects, and the majority of them have shown a dose-dependent protective role. On the other hand, there is relatively limited evidence regarding the in vitro antioxidant effects of antidiabetic drugs on pancreatic β -cells. Concerning in vivo studies, several natural extracts have shown beneficial effects in the setting of diabetes by decreasing blood glucose and lipid levels, increasing insulin sensitivity, and by up-regulating intrinsic antioxidant enzyme activity. However, there is limited evidence obtained from in vivo studies regarding antidiabetic drugs. Conclusion: Antioxidants hold promise for developing strategies aimed at the prevention or treatment of diabetes mellitus associated with pancreatic β-cells dysfunction, as supported by in vitro and in vivo studies. However, more in vitro studies are required for drugs.
Keywords: pancreatic β-cells